Time of day effect on athletic performance: An update - Cappaert, T. A. (The Journal of Strength and Conditioning Research, 1999)
Various psychological and physiological functions have been shown to undergo changes relative to the time of the solar day. These variations are known as circadian or diurnal rhythms. These functions exhibit peaks and troughs of maximum and minimum function at specific times of the day. Many components related to athletic performance have been shown to possess these circadian rhythms. A literature search was performed using the databases Medline, SPORTDiscus, and the Cumulative Index to Nursing and Allied Health Literature. Keywords used in the search were "circadian rhythm and exercise" and "diurnal variations and exercise". Articles were used if they were related to athletic performance and/or testing and were published after 1985. The articles were then separated into the broad subjects of time of day effects on acute responses to exercise, chronic responses to exercise, and effect of chronotype on exercise. The conclusions reached were that a probable time of day effect is present for the following conditions: isotonic and isokinetic strength measures, anaerobic power and capacity, and body temperature and exercise response. A more equivocal relationship was found between time of day and endurance training, ratings of perceived exertion, chronotype and exercise, arm exercise, and self-paced exercise.